Innovation and Creativity in Handling Cases of Domestic Violence from Victimology Perspective - Dhinarta, Aldhito Bagus (Journal of Creativity Student, 2019)
Domestic Violence is always happens to women. As time goes on, domestic violence is increasing, so there must be legal protection for victims of domestic violence. Domestic violence certainly makes its victims suffer and suffer. In marriage, every couple dreams of forming a harmonious, happy and loving family, but in reality many families are not harmonious, but because of domestic violence, whether physical, psychological or psychological, everyone feeling depressed and sad. Emotional or family abandonment. Domestic violence (KDRT) can be caused individually or collectively by internal and external factors. Especially in the era of openness and advances in information technology, violent behavior often appears through media that do not filter out its negative effects. It is necessary to socialize the law in the community so that people realize that all forms of domestic violence are crimes, so that the community, especially wives, are not afraid to report crimes to the police.